2009
DOI: 10.1038/ijo.2009.208
|View full text |Cite
|
Sign up to set email alerts
|

Leptin is essential in maintaining normal vascular compliance independent of body weight

Abstract: The adipocytokine leptin centrally regulates body weight by enhancing metabolic rate and signaling satiety, but it also has wideranging peripheral effects. Leptin receptors are expressed on vascular smooth muscle cells and have a role in maintaining vascular tone. We investigated the vascular effects of leptin repletion or calorie restriction on leptin-deficient mice (ob/ob) and a leptin antagonist on wild-type (WT) mice. Aortic compliance was assessed by the measurement of pulse wave velocity by noninvasive D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…For example, older (7-9 months old) and younger (2.5-3 months old) ob/ob mice, as well as db/db mice, exhibited higher aortic PWVs and lower aortic compliance. [23][24][25] In addition, mechanical testing of the aortas from obese Zucker (fa/fa) rats showed greater stiffness in the circumferential and longitudinal directions. 26 However, the mechanistic insight into the link between obesity and aortic stiffening has been lacking.…”
Section: Discussionmentioning
confidence: 99%
“…For example, older (7-9 months old) and younger (2.5-3 months old) ob/ob mice, as well as db/db mice, exhibited higher aortic PWVs and lower aortic compliance. [23][24][25] In addition, mechanical testing of the aortas from obese Zucker (fa/fa) rats showed greater stiffness in the circumferential and longitudinal directions. 26 However, the mechanistic insight into the link between obesity and aortic stiffening has been lacking.…”
Section: Discussionmentioning
confidence: 99%
“…However, data are not available in nondiabetic humans, in part because long-term caloric restriction is difficult to achieve in humans. Short-term low-calorie diet caused weight reduction and successfully reduced arterial stiffness and increase vascular compliance in ob / ob mice [40] and obese men [41] when given for 4 and 12 weeks, respectively. Because of the short duration of this intervention, it is likely that the reduced arterial stiffness is primarily due to the lowering of vascular resistance in the smaller vessels rather than slowing down the stiffness of the larger ones.…”
Section: Caloric Restrictionmentioning
confidence: 96%
“…Whether hyperleptinemia in obesity and OSA serves a protective role or causes detrimental effects in the cardiovascular system is still under debate. While some suggest that elevated leptin induces oxidative stress and sympathetic overactivation (20, 42), others have found the insulin-sensitizing and lipid lowering actions of leptin to be cardioprotective (31, 46).We have previously shown that vascular and myocardial abnormalities in leptin-deficient ob/ob animals are attributable to the disruption of intact leptin signaling independent of body weight (4,28,43). Because IH exposure leads to exacerbation of well-established cardiovascular risk factors of hyperlipidemia and insulin resistance (17,26), and ob/ob animals lack leptin-mediated protection against these developments, we hypothesized that IH may disrupt normal leptin signaling in WT and result in worsening of lipid-induced injury in ob/ob, leading to further exacerbation of cardiovascular function.…”
mentioning
confidence: 99%